2015
DOI: 10.1108/jaee-04-2011-0011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of income smoothing on earnings quality in emerging markets

Abstract: The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we will investigate on a case-by-case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
3
21
2
Order By: Relevance
“…The present study found accruals-based measures to be better than the time-series measures, smoothness measures, however, outperformed accruals measures in predicting market returns. Unlike Shubita (2015), Dawar (2014) and Ganguli (2011) who found no significant impact of smoothing on market returns in India, the present study found significant negative hedge returns on portfolios based on smoothness measures which was 9% for EQ-3 and 15% for EQ-4 significant at 5% and 1%, respectively. Negative sign of the hedge returns suggests that earnings smoothing in India is opportunistic than informational.…”
Section: Resultscontrasting
confidence: 93%
“…The present study found accruals-based measures to be better than the time-series measures, smoothness measures, however, outperformed accruals measures in predicting market returns. Unlike Shubita (2015), Dawar (2014) and Ganguli (2011) who found no significant impact of smoothing on market returns in India, the present study found significant negative hedge returns on portfolios based on smoothness measures which was 9% for EQ-3 and 15% for EQ-4 significant at 5% and 1%, respectively. Negative sign of the hedge returns suggests that earnings smoothing in India is opportunistic than informational.…”
Section: Resultscontrasting
confidence: 93%
“…This implies that smoothing carried out by Nigerian firms appears to be deliberate rather than natural, and investors priced firms' shares that engaged in smoothing, particularly intentional smoothing low. Also, smoothening income reduces the shock/ surprise in the market when the reported income by managers meets investors' forecasted income (Baik et al, 2019;Bartov et al, 2002;Chen et al, 2016;Lyimo, 2014;Oler et al, 2016;Shabani and Sofian, 2018;Shubita, 2015). This result is similar to the findings of Chen et al (2016); Novianti and Firmansyah (2020); Susanto andPradipta, 2019, andYu et al (2017) which revealed that investors perceive smoothing as an increase in risk and a means of managerial opportunism resulting in reduced firm value.…”
Section: Discussionsupporting
confidence: 77%
“…Although most studies generally use earnings smoothing as a proxy for earnings management (Bhattacharya et al, 2003;Burgstahler et al, 2006;Leuz et al, 2003), some studies find that earnings smoothing in fact is associated with improved earnings quality (Ewert & Wagenhofer, 2015;Shubita, 2015;Subramanyam, 1996;Tucker & Zarowin, 2006). Hence, it comes to no surprise when prior literatures reveal that the studies on the role of earnings smoothing are divided into two streams: as information signaling and information garbling.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, scholars have been trying to prove the existence of earnings smoothing activities (Beidleman, 1973;Boterenbrood, 2014;Khalil & Simon, 2014), figuring how (Atik, 2009;Francis et al, 2016) and when (Gassen et al, 2006;Gill de Albornoz & Alcarria, 2003) managers smooth earnings, characterizing earnings smoothing firms Bouwman, 2014;Z. Huang & Xue, 2016;Safdar & Yan, 2016;Silhan, 2014), and most importantly understanding the motivation (Goel & Thakor, 2003;Lambert, 1984;Trueman & Titman, 1988) and consequences (Houcine, 2017;Shubita, 2015;Tucker & Zarowin, 2006) of such behavior. This paper aims to review prior literatures, specifically on the role of earnings smoothing.…”
Section: Introductionmentioning
confidence: 99%